2009
DOI: 10.1159/000258639
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Brain-Derived Neurotrophic Factor Val66Met Polymorphism and Recent Negative Stressor in Harm Avoidance

Abstract: There have been controversial results regarding the association between brain-derived neurotrophic factor (BDNF) Val66Met polymorphism and anxiety-related traits such as harm avoidance (HA). We aimed to investigate the interaction between BDNF Val66Met polymorphism and negative life stressors in HA. BDNF Val66Met polymorphism was genotyped in 391 community-dwelling Koreans (152 males, 239 females; 43.2 ± 14.1 years old). The Temperament and Character Inventory (TCI) and the Center for Epidemiological Studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 76 publications
3
26
1
Order By: Relevance
“…Our findings are also not in agreement with G x E studies that found an interactive effect of the higher functioning Val66 allele and environmental exposures (i.e. adversity, negative stressors, recent life events) on psychopathology, such as increased levels of neuroticism, harm avoidance and depression (Chen et al, 2013; Kim et al, 2009; Lehto et al, 2016). Apart from the possible confounding effects of age and gender, discrepant results across studies may in part be due to population-driven differences in BDNF Val66Met frequencies, given that the Met66 allele has consistently been found to be more common in Asian populations than in Caucasian populations (Chen et al, 2013; Petryshen et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are also not in agreement with G x E studies that found an interactive effect of the higher functioning Val66 allele and environmental exposures (i.e. adversity, negative stressors, recent life events) on psychopathology, such as increased levels of neuroticism, harm avoidance and depression (Chen et al, 2013; Kim et al, 2009; Lehto et al, 2016). Apart from the possible confounding effects of age and gender, discrepant results across studies may in part be due to population-driven differences in BDNF Val66Met frequencies, given that the Met66 allele has consistently been found to be more common in Asian populations than in Caucasian populations (Chen et al, 2013; Petryshen et al, 2009).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, these results extend findings of the role of BDNF and CM on AS. Previous studies have focused on convenience samples of college students, or adults, and predominantly on the effects of the 5-HTTLPR polymorphism (Hemmings et al, 2016; Kim et al, 2009; Klauke et al, 2011; Laucht et al, 2009; Stein et al, 2008). Our results suggest that the influence of CM on adolescent AS levels is not moderated by the BDNF Val66Met polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders lead to profound suffering and disability that can markedly disrupt family life as well as the life of the sufferer, especially when associated with avoidance behavior and agoraphobia (Gray and McNaughton, 2000;Nutt, 2005;Kim et al, 2010). Although attenuated theta rhythms have been observed in human subjects with increased anxiety (Mizuki et al, 1989;Suetsugi et al, 2000), this phenomenon has not been replicated in animal models of anxiety disorders (Mitchell et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, no main effects of BDNF Val66Met on personality could be observed in this study. A BDNF Val66Met by early life stress interaction effect was reported by Gatt et al [128]: In contrast to Kim et al [76], they found evidence for the 66Met allele to be the vulnerability factor for neuroticism under high early life stress. Again, it is of importance to keep in mind that the studies differed in terms of measured stress (recent life stress versus early life stress) and also with respect to ethnicity.…”
Section: Interaction Effects Of Bdnf Val66met and Environmental Influmentioning
confidence: 75%
“…Following from this seminal finding, several studies ensued investigating gene by environmental effects also with a focus on personality (e.g., [20,[125][126][127]). Focusing on the BDNF gene, Kim et al [76] reported that carriers of the homozygous Val66Val variant under the influence of negative stressors reported higher harm avoidance scores. Notably, no main effects of BDNF Val66Met on personality could be observed in this study.…”
Section: Interaction Effects Of Bdnf Val66met and Environmental Influmentioning
confidence: 99%